Musculoskeletal manifestations of childhood cancer and differential diagnosis with juvenile idiopathic arthritis (ONCOREUM): a multicentre, cross-sectional study. (July 2021) - Civino, Adele; Alighieri, Giovanni; Prete, Eleonora; Caroleo, Anna Maria; Magni-Manzoni, Silvia; Vinti, Luciana; Romano, Micol; Santoro, Nicola; Filocamo, Giovanni; Belotti, Tamara; Santarelli, Francesca; Gorio, Chiara; et al.
Summary: Background: Presenting symptoms of childhood cancers might mimic those of rheumatic diseases. However, the evidence available to guide differential diagnosis remains scarce. Preventing wrong or delayed diagnosis is therefore important to avoid incorrect administration of glucocorticoid or immunosuppressive therapy and worsening of prognosis. As such, we aimed to assess the prevalence and characteristics of presenting musculoskeletal manifestations in patients at cancer onset and to identify the factors that differentiate childhood malignancies with arthropathy from juvenile idiopathic arthritis. Methods: We did a multicentre, cross-sectional study at 25 paediatric haemato-oncology centres and 22 paediatric rheumatology centres in Italy. We prospectively recruited patients who were younger than 16 years that were newly diagnosed with cancer or juvenile idiopathic arthritis. We excluded patients with glucocorticoid pre-treatment (>1 mg/kg per day of oral prednisone or equivalent for ≥2 consecutive weeks). We collected data for patients with a new diagnosis of cancer or juvenile idiopathic arthritis using an electronic case report form on a web-based platform powered by the Cineca Interuniversity Consortium. The primary outcome was to describe the frequency and characteristics of musculoskeletal manifestations at cancer onset; and the secondary outcome was to identify factors that could discriminate malignancies presenting with arthropathy, with or without other musculoskeletal symptoms, from juvenile idiopathic arthritis using multivariable logistic regression analysis. Findings: Between May 1, 2015, and May 31, 2018, 1957 patients were eligible, of which 1277 (65%) had cancer and 680 (35%) had juvenile idiopathic arthritis. Musculoskeletal symptoms occurred in 324 (25% [95% CI 23·0–27·8]) of 1277 patients with cancer, of whom 207 had arthropathy. Patients with malignant bone tumours had the highest frequency of musculoskeletal symptoms (53 [80%] of 66), followed by patients with Langerhans histiocytosis (16 [47%] of 34), leukaemia (189 [32%] of 582), soft-tissue sarcomas (16 [24%] of 68), and neuroblastoma (21 [19%] of 109). In the 324 patients with cancer and musculoskeletal symptoms, the most common complaints were joint pain (199 [61%]), followed by limb bone pain (112 [35%]). Joint involvement had a prevalent monoarticular pattern (100 [48%] of 207) and oligoarticular pattern (86 [42%] had 2–4 joints involved and 20 [10%] had >4 joints involved), with the most frequently involved joints being the hip (88 [43%] of 207) and knee (81 [39%]). On multivariable analysis, limb bone pain was the independent variable most strongly associated with cancer (odds ratio [OR] 87·80 [95% CI 18·89–408·12]), followed by weight loss (59·88 [6·34–565·53]), thrombocytopenia (12·67 [2·40–66·92]), monoarticular involvement (11·30 [4·09–31·19]), hip involvement (3·30 [1·13–9·61]), and male sex (2·40 [1·03–5·58]). Factors independently associated with juvenile idiopathic arthritis were morning stiffness (OR 0·04 [95% CI 0·01–0·20]), joint swelling (0·03 [0·01–0·09]), and involvement of the small hand joints (0·02 [0–1·05]). Interpretation: Our study provides detailed information about presenting musculoskeletal manifestations of childhood cancers and highlights the clinical and laboratory features that are most helpful in the differential diagnosis with juvenile idiopathic arthritis. Funding: Associazione Lorenzo Risolo.